2013
DOI: 10.2174/1874331501307010040
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity Under Different Tillage and Crop Rotation Systems in an Oxisol of Southern Brazil

Abstract: Microbial diversity can be used to assess the impact of agricultural practices on the long-term sustainability of cropping systems. The aim of this study was to investigate changes in soil bacterial diversity as a result of the impact of different soil tillage and crop rotation systems in an oxisol of southern Brazil. Bacterial diversity was examined in the 0-10 cm layer in two field experiments by analyzing soil DNA using 16S rDNA-DGGE profiles. Experiment one consisted of a long-term 26-year trial with four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
5
22
1
4
Order By: Relevance
“…These findings are consistent with those reported by Mathew et al (2012) and Peixoto et al (2006). Moreover, Silva et al (2013) reported that in a long-term field experiment, the DNA profiles representative of each tillage treatment showed differences in soil bacterial diversity, with greater diversity under NT, compared to the other systems studied, inter alia CT. The dendrogram derived from the 16S rDNA DGGE profiles also revealed the effect of tillage system choice on the overall bacterial community structure in different depths of soil profile (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with those reported by Mathew et al (2012) and Peixoto et al (2006). Moreover, Silva et al (2013) reported that in a long-term field experiment, the DNA profiles representative of each tillage treatment showed differences in soil bacterial diversity, with greater diversity under NT, compared to the other systems studied, inter alia CT. The dendrogram derived from the 16S rDNA DGGE profiles also revealed the effect of tillage system choice on the overall bacterial community structure in different depths of soil profile (Fig.…”
Section: Resultssupporting
confidence: 91%
“…8). Soil under systems with lower soil disturbance such as the NT system could also protect microbial habitats by increasing the soil organic matter concentration, enhancing soil moisture content and decreasing temperature variations, all of which affect soil microbial diversity (Silva et al, 2013). Moreno et al (2009) Explanations as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although not significantly, microbial species under NT were slightly more abundant within the microbial community, i.e., lower dominance, compared to microbial species under CT (Figure 6b). This slightly higher level of dominance of certain soil microbial species found in microbial communities under CT could be attributed to the disruption of microbial development and establishment due to tillage [50]. This would typically cause the strongest and more adaptable microorganisms to establish and flourish first.…”
Section: Soil Microbial Functional Diversitymentioning
confidence: 97%
“…The primers used were F-968 (5´CGCCCGGGGCGCGCCCCGGGCGGGGCGGGGGCACGGGGGGAACGCGAAGAACCTT AC-3), with the GC clamp and R-1401 5´-GCGTGTGTACAAGACCC-3) (NŪBEL et al, 1996). The amplification reaction was carried out according to SILVA et al (2013). Gels were stained with ethidium bromide (0.3 μg m L -1 ) and visualized with UV light.…”
Section: Diversity Of the Soil Bacte Rial Communitymentioning
confidence: 99%